2011
DOI: 10.1590/s0100-06832011000400024
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of phosphorus sorption in soils in the state of Paraíba¹

Abstract: SUMMARYThe soil P sorption capacity has been studied for many years, but little attention has been paid to the rate of this process, which is relevant in the planning of phosphate fertilization. The purpose of this experiment was to assess kinetics of P sorption in 12 representative soil profiles of the State of Paraíba (Brazil), select the best data fitting among four equations and relate these coefficients to the soil properties. Samples of 12 soils with wide diversity of physical, chemical and mineralogical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
12
0
3
Order By: Relevance
“…Santos et al (2011) found that adsorption of 74% of the added P occurred within 5 min in soil with a high P sorption capacity (0.3473 mg g -1 ). More recently, Guedes et al, (2016) studying P adsorption and desorption kinetics using a stirred-flow system, observed that most of the P adsorption process occurs in the first minutes of contact with the solution.…”
Section: Introductionmentioning
confidence: 97%
“…Santos et al (2011) found that adsorption of 74% of the added P occurred within 5 min in soil with a high P sorption capacity (0.3473 mg g -1 ). More recently, Guedes et al, (2016) studying P adsorption and desorption kinetics using a stirred-flow system, observed that most of the P adsorption process occurs in the first minutes of contact with the solution.…”
Section: Introductionmentioning
confidence: 97%
“…(1) According to methodology described in EMBRAPA (1997); (2) Data presented in Santos et al (2011), according to EMBRAPA (2006: RR -Regolithic Neosol, PAC -Grey Argisol; TX -Haplic Luvisol; PVA -Red-Yellow Argisol; PVd -Dystrophic Red Argisol; VX -Haplic Vertisol; (3) Remaining phosphorus (Alvarez V. et al, 2000); (4) The experiment was carried out in a randomized block design with 6 soil classes, 7 incubation times and 4 doses, with three replicates; each experimental unit consisted of one polyethylene pot without drain, with 2.8 dm 3 of soil and two maize plants.…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, most soils have high maximum phosphate adsorption capacity (MPAC) and high contents of Fe and Al oxides, characteristics that are different from those of soils of the Northeast region. Therefore, it raises the hypothesis that, in Northeast soils, P sorption exists, but the magnitude and irreversibility of this sorption are small (Broggi et al, 2010;Santos et al, 2011;Souza Júnior et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is also to be considered that the soil composition of the accessible and inner part of the aggregates might differ from the fine earth. The, in general, great heterogeneity of soil in physical, chemical, and mineralogical aspects in the solid-state, and also regarding soil solution, has to be considered in explaining the data [22,52]. Although the sorption process is predominantly assumed to be a surface phenomenon [25,53], structured soils may withdraw molecules from the advectively moving soil water.…”
Section: Sorption Isothermsmentioning
confidence: 99%